OPTIMIZATION OF APPARATUS RESOURCES IN IMPROVING GOVERNANCE IN SAWADAI VILLAGE, SOUTH BACAN AND LABUHA VILLAGE, BACAN CAPITAL - Rifaldi Hairil; Syahril Muhammad; Misrina (SOSIOEDUKASI, 2026)
Optimizing village apparatus resources is an important factor in improving effective, transparent, and accountable village governance. This study aims to analyze the optimization of apparatus resources in improving governance in Sawadai Village, South Bacan District and Labuha Village, Bacan Capital City. The research method used is a qualitative method with a descriptive approach. Data collection techniques are carried out through interviews, observations, and documentation. The results of the study show that the optimization of village apparatus resources has not been fully optimal, which is characterized by limited apparatus competence, lack of training, and not yet optimal use of information technology in the implementation of village government. However, there are efforts from the village government to increase the capacity of the apparatus through training and coaching. The conclusion of this study shows that improving the quality of village apparatus resources needs to be supported by continuous training, clear division of tasks, and support for facilities and infrastructure to realize good village governance.